The Goonies - Donner, Richard (Steven Spielberg, 1985)
The Goonies plunges a band of small heroes into a swashbuckling, surprise-around-every-corner quest beyond their wildest dreams. Following a mysterious treasure map into a spectacular underground realm of twisting passages, outrageous booby-traps and a long-lost pirate ship full of golden doubloons, the kids race to stay one step ahead by a family of bumbling bad guys... and a mild mannered monster with a face only a mother could love.